Cathodic debonding of undersea electronic cable connectors: Delamination kinetics when primers and encapsulants are bonded directly to bare metal connector backshells - Ramotowski, Thomas S.; Tucker, Wayne C.; Rice, Matthew A. (2013 OCEANS-San Diego : 23-27 September 2013, 2013)
When undersea cable connectors are attached to receptacles that are part of a cathodically protected vessel hull, the encapsulants applied over the connector backshells to protect the interior of the connector from seawater ingression often rapidly debond from the backshell, thereby compromising the interior of the cable and connector. This process is called "cathodic delamination" or "cathodic disbondment" and it is believed to be caused by the generation of highly alkaline conditions at the metal-encapsulant bondline due to the reduction of dissolved oxygen and the subsequent generation of hydroxyl (OH-) ions. An investigation into the kinetics of this process for the case where encapsulants and their associated primers are bonded directly to bare metal connector backshells was undertaken to develop better accelerated life testing techniques for marine hardware subject to cathodic delamination. Two different commercial encapsulation systems were investigated: PR-420 primer/PR-1547 polyurethane (PRC-DeSoto) and AD-1146 primer/EN-1556 polyurethane (Cytec). Small sacrificial zinc anodes were used to provide the proper cathodic polarization for the test samples. This testing revealed that cathodic debonding preferentially proceeds from exposed edges/bondlines inward, rather than through the encapsulant. Some primer/encapsulant systems (e.g., the PRC-Desoto system) are inherently more resistant to cathodic delamination that other systems. The rate at which the debonding proceeds was found to be diffusion controlled and was linear when plotted versus the square root of elapsed time. Debonding rate data were used to determine the Arrhenius activation energy for the cathodic delamination of both encapsulation systems (8.4 kcals/mole for the PRC-DeSoto system and 2.6 kcals/mole for the Cytec system), which are quite different from the experimentally determined Arrhenius activation energies for the diffusion of water through the various encapsulants (3.1 kcals/mole and 3.9 kcals/mole, respectively). These results suggest that the cathodic delamination process for undersea electronic cable connectors is controlled by the rate of water and dissolved species diffusing along the disrupted bondline, rather than by water the rate of water and oxygen diffusing through the encapsulant.